El estudio del Derecho internacional en el corto siglo XIX español - De la Rasilla, Ignacio 1975- (Rechtsgeschichte, 2013)
Oriented to provide a broad backdrop image of the cultivation of ius-internationalist studies in the Nineteenth Century Spain, the first part of this work revisits the suppression of studies of the Law of Peoples during the last part of the Eighteenth century and hints at some of ist developments during the first third of the Nineteenth century before examining the establishment in. The early 1840s of the first chairs of international law in Europe against the background of the independence of the Latin-American Republics and relates the development of Spanish international law production during the first half of the nineteenth century. The second part follows the character of the evolution of international legal studies in Spain until the year 1883 when chairs in Public International Law and Private International Law outside Madrid were established in seven other Spanish universities. The third part reviews the - albeit short-lived- first specialized international law journal ever established in Spain, and examines how Spanish production in the field was fostered by the professionalization reform of 1883. This part also deals with the Salamanca School's parallel rediscovery in both Spain and Europe in the last third of the short Spanish nineteenth century. The impact that the revival of interest in Francisco de Vitoria had in providing Spanish international law academia with a quasi-national identity leads to some conclusions on ist lasting legacy to the study of international law in the cradle of the first Empire in history on which the sun never set.